Peran Guru dalam Membangun Kompetensi Siswa melalui Pendekatan Pemecahan Masalah di Sekolah Dasar - Anim Purwanto; Dudi Ruhyadi Muharam; Agus Dwi Pryitno; Muhammad Faisal; Istiqomah, Istiqomah (Yayasan Literasi Sains Indonesia, 2024)
This research aims to answer the question of how teachers play a role in building students' competencies through a problem-solving approach at Jagakarsa 04 Morning Public Elementary School in Jakarta. The study utilizes a qualitative approach with a case study design, where the researcher explores information on the topic under investigation. Data is collected through classroom observations and interviews with 4 teachers serving as informants. The collected data is thematically analyzed, where the researcher identifies patterns and main themes emerging from the data. The research findings indicate that the role of teachers in developing students' competencies through a problem-solving approach is crucial. Teachers not only act as facilitators helping students acquire skills through this approach but also serve as models providing good examples in problem-solving. Additionally, teachers support collaboration and teamwork among students, strengthening their problem-solving abilities collectively. Teachers also play a key role in encouraging students to develop creativity and innovation through the problem-solving approach, enhancing their critical and solution-oriented thinking skills. Lastly, teachers create a safe and supportive learning environment, allowing students to independently explore task solutions. These findings contribute new insights for teachers to optimize their roles in fostering students' competencies through a problem-solving approach in elementary schools.